Cues to Care: Are city landowners willing to make ecological landscapes? - Mark Hostetler (EDIS)
The purpose of this fact sheet is to inform homeowners, developers, and city officials about potential considerations to make urban landscapes more eco-friendly, to improve urban biodiversity, and to explore avenues to install more environmentally friendly landscapes that provide wildlife habitat and reduce natural resource consumption.